Whoops! - Moore, Suzi (British author); Ayto, Russell (Somerville, Mass. : Templar Books, an imprint of Candlewick Press, 2016)
The cat can't meow, the dog can't bark, and even the mouse can't squeak. When they go to the little old lady in the woods for a spell to restore their voices, things don't go as expected.
Keywords: Animal sounds -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Incantations -- Juvenile fiction; Mice -- Juvenile fiction; Stories in rhyme